Optimal monetary policy in the generalized Taylor economy - Engin Kara (European Central Bank (ECB), 2006)
In this paper we use the Generalized Taylor Economy (GTE) framework in which there are many sectors with overlapping contracts of different lengths to analyze the design of monetary policy. We derive a utility based objective function of a central bank for this economy and use it to evaluate the performance of alternative simple rules. We find that a simple rule that targets an index that gives more weight to the sectors which have longer contracts and are more important in the aggregate index yields a welfare outcome nearly identical to the optimal policy. However, we find that potential gains in targeting sector specific inflation rates rather than the aggregate inflation rate is very sensitive to the shape of the distribution. We show that except for the cases where prices/wages are reoptimized very frequently, the performance of the sectoral rule can be closely approximated by a simple rule that targets aggregate inflation.
Keywords: E32; E52; E58; 330; inflation targeting; Optimal Monetary Policy; Inflationssteuerung; Geldpolitisches Ziel; Zentralbank; Inflationssteuerung; Theorie